Demineralisasi Batubara Berkadar Abu Tinggi dengan Leaching Menggunakan Alkali - Ikhsana, Mifta Aulia; Azis, Muhammad Mufti; Purwono, Suryo (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The study was comdustred on the demineralization of Jambi coal with high ash content as an effort to improve quality. The coal selected first crushed to -80 + 115 mesh. Demineralization was carried out using leacjing process with NaOH 20, 25, and 30% (%weight). The best parameter was used in subsequent leaching process to determine the effect of temperature of 50, 70, 90oC. The result showed that the percentage of demineralization increased with increasing demineralization reduction 34%